2014
DOI: 10.1016/j.freeradbiomed.2014.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-1 redox signaling regulates cell survival in response to hyperoxia

Abstract: The most common form of newborn chronic lung disease, bronchopulmonary dysplasia (BPD), is thought to be caused by oxidative disruption of lung morphogenesis which results in decreased pulmonary vasculature and alveolar simplification. Although cellular redox status is known to regulate cellular proliferation and differentiation, redox-sensitive pathways associated with these processes in developing pulmonary epithelium are unknown. Redox sensitive pathways are commonly regulated by cysteine thiol modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 112 publications
(97 reference statements)
1
38
0
Order By: Relevance
“…In the intracellular compartment, TRX-1 was mainly present as nonfully oxidized forms in basal conditions. In this respect, there have been previous papers showing only the reduced form of TRX-1 in basal conditions [24,[42][43][44][45], while others also ͳͳ showed the two bands observed in the present paper [46,47]. Technical questions and/or culture conditions could account for these potential discrepancies since it has been demonstrated that proliferative status [48] or ion composition [49] could modify TRX-1 oxidative status.…”
Section: Discussionsupporting
confidence: 47%
“…In the intracellular compartment, TRX-1 was mainly present as nonfully oxidized forms in basal conditions. In this respect, there have been previous papers showing only the reduced form of TRX-1 in basal conditions [24,[42][43][44][45], while others also ͳͳ showed the two bands observed in the present paper [46,47]. Technical questions and/or culture conditions could account for these potential discrepancies since it has been demonstrated that proliferative status [48] or ion composition [49] could modify TRX-1 oxidative status.…”
Section: Discussionsupporting
confidence: 47%
“…Therefore, it is not surprising that our data showed novel targets of Trx1 that lie in the nucleus, including ATP-dependent RNA helicase DDX3X (Ddx3x), guanine nucleotide-binding protein subunit beta-2-like-1 (Gnb2l1), heterogeneous nuclear ribonuclear protein A3, and 40S ribosomal protein S3a (Rps3a). Studies have shown that hyperoxia causes Trx1 oxidation [17, 68]. This data indicates that the reactive Cys32 of the flag-hTrx1 C35S under high oxygen conditions could be oxidized, which may explain why fewer targets of Trx1 were identified in this cohort.…”
Section: Discussionmentioning
confidence: 67%
“…Endogenous expression of a Trx1 protein where the Cys35 residue is mutated to serine creates a stable intermediate between thioredoxin and its substrate and these complexes are then analyzed with mass spectrometry. We have successfully used this technique for proteomic identification of novel Trx1 substrates in lung adenocarcinoma cells [17]. We have taken this method one step further and created a novel transgenic mouse model that expresses the Trx1 substrate trap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations